Revisiting Trust in Symbolic Interaction: Presentations of Trust Development in University Administration - Gawley, Tim (Qualitative Sociology Review, 2007)
Trust development has been studied from many sociological perspectives. Despite its early ventures, a perspective that lags in its attendance to trust is symbolic interaction. Using data drawn from twenty four semi-structured interviews with Canadian university administrators (UAs), this paper revisits a Goffman-influenced conceptualization proposed by Henslin (1968) to frame the analysis of four trust development tactics: being visible, expressing sincerity and personalization, showing the face and establishing routine activity. Resistance encountered during trust development is also discussed. Findings are compared with previous studies of trust in professional, leadership and everyday life settings. The implications of this paper for future symbolic interactionist forays into the areas of trust and administration are also discussed.